Kepastian Hukum Penerapan Asas Audi et Alteram Partem dalam Pemeriksaan Perkara Perdata Secara Elektronik (E-Court) - Moulyta Elgi Trinanda; Queena Allysa Kinanti; Lira Ayu Anggraini (Pusat Riset dan Inovasi Nasional, 2026)
The digital transformation of Indonesia’s judicial system through the implementation of e-court represents a judicial reform aimed at achieving a simple, fast, and low-cost legal process. However, the digitization of civil case proceedings raises concerns regarding legal certainty, particularly in the application of the principle of audi et alteram partem as a fundamental doctrine ensuring equal opportunity for parties to be heard. This study aims to analyze the normative regulation of the audi et alteram partem principle in Indonesian civil procedural law, examine its implementation within the e-court system, and assess whether its application provides adequate legal certainty for litigants. The research employs a normative juridical method using statutory and conceptual approaches. Legal materials consist of statutory regulations, legal doctrines, and relevant academic journals. The findings indicate that normatively, the e-court system accommodates the right to be heard through electronic case registration, summons, hearings, and submission of documents. Nevertheless, technical obstacles, disparities in digital literacy, and potential deficiencies in electronic notification mechanisms may affect the effective protection of parties’ rights. It is concluded that the implementation of the audi et alteram partem principle in e-court has a sufficient legal foundation, yet requires further technical and regulatory strengthening to ensure optimal legal certainty.